Methods of Developing Research Skills Through Interactive Digital Laboratories in Physics Education - Qoraboyev Xusniddin Soxibjonovich (Scientific Trends, 2025)
This article presents with a simple and systematic approach the methodology for developing students' research skills through interactive digital laboratories in teaching physics. In the changing information and communication environment in modern pedagogical conditions, it remains important for students to independently form their knowledge, conduct experiments, collect information, analyze and draw conclusions. Interactive digital labs (e.g. simulations, virtual experiments, digital touch modules) create a methodologically efficient platform to support this process. Firstly, the article explains the role and basic principles of digital laboratories in the educational process, the second is the structure and basic stages of research skills, and the third is the system of methodological recommendations for the formation of these skills using interactive digital laboratories. Also on practical terms, model stages and problems, as well as measures to overcome them are addressed. This approach serves to awaken students' scientific thinking in the world of pedagogy and physics education and to stimulate independent research.
Keywords: Physics education, digital lab, interactive experiment, research skills, visual-modeling, teaching methods, virtual lab, independent student activity.